1996
DOI: 10.1113/jphysiol.1996.sp021536
|View full text |Cite
|
Sign up to set email alerts
|

Calorigenic effect of diiodothyronines in the rat.

Abstract: 1. In hypothyroid rats, we determined the effects of administration of different doses of 3,3',5-triiodo-L-thyronine (T3), 3,3'-diiodo-L-thyronine (3,3'-T2) and 3,5-diiodo-L-thyronine (3,5-T2) ('T2 isomers' refers specifically to these latter two isomers throughout this paper) on resting metabolism (RM) and on the oxidative capacity (measured as cytochrome oxidase activity) of tissues that are metabolically very active. 2. The T2 isomers induced a dose-dependent calorigenic effect when injected i.P. into hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 35 publications
4
88
1
Order By: Relevance
“…In addition, the rats received an i.p. injection of iopanoic acid (IOPA; 6 mg/100 g body weight) (Lanni et al 1996) once a week. PTU blocks thyroidal hormone synthesis via inhibition of thyroid peroxidase activity, and it is also a strong inhibitor of type I 5 0 -D-deiodinase activity (Oppenheimer et al 1972, Leonard & Visser 1986.…”
Section: Animals and T 3 Determinationmentioning
confidence: 99%
“…In addition, the rats received an i.p. injection of iopanoic acid (IOPA; 6 mg/100 g body weight) (Lanni et al 1996) once a week. PTU blocks thyroidal hormone synthesis via inhibition of thyroid peroxidase activity, and it is also a strong inhibitor of type I 5 0 -D-deiodinase activity (Oppenheimer et al 1972, Leonard & Visser 1986.…”
Section: Animals and T 3 Determinationmentioning
confidence: 99%
“…Resting metabolism was measured by indirect calorimetry, as previously reported (27) and thyroid hormone serum levels were measured by radioimmunoassay (Becton-Dickinson, Orangenburg, NJ, USA).…”
Section: Resting Metabolism and Thyroid Hormone Levels In Serummentioning
confidence: 99%
“…In addition, since we found that some morphological signs are indicative of cell death by apoptosis, we compared both mitochondrial and cytosolic expression of cytochrome c [the principal initiator molecule released from mitochondria to cytosol to initiate the apoptotic program in cells (Green and Reed, 1998)] in euthyroid and hypothyroid rat HGs. (Lanni et al, 1996). Control rats (N=8) received saline injections.…”
Section: Introductionmentioning
confidence: 99%